An Approach for Simple Linear Profile Gauge R&R Studies - Liangxing Shi; Wei Chen; Liang Fu Lu (Discrete Dynamics in Nature and Society)
Gauge repeatability and reproducibility studies are significant to quality improvement and quality control. The approaches are always applied to determine the capability of the measurement system. Much of the literature in this field mainly focuses on univariate and multivariate measurement systems. However, the state-of-the-art methods are not appropriate when the quality of a product is characterized by a profile. Therefore, this paper proposes a method for the measured values which can be characterized by a simple linear profile. In addition, the slopes and intercepts of these profiles often vary due to measurement error. Thus, the simple linear profile gauge studies can be considered as a two-response (slope and intercept) problem. X-values transformation is used to make the slope and intercept of each profile independent. ANOVA is utilized to estimate the variance component of measurement error and other sources of variation. Then, the criteria precision to tolerance ratio and percent R&R are introduced to assess the simple linear profile measurement system capability. Finally, the proposed approach is applied to the spring length and elasticity measurement which demonstrates how to implement the method.